Improving Postpartum Care Through Nursing Interventions: A Focus on Mental Health, Breastfeeding Support, and Physical Recovery - Binesha P.B.; Regina P.F.; Dana Baby; Yamuna Devi (International Journal of Midwifery Nursing And Practices, 2025)
Postpartum care is a vital phase that requires a comprehensive approach to addressing mothers' physical, emotional, and psychological needs. Nursing interventions, which focus on mental health, breastfeeding support, and physical recovery, play a critical role in enhancing postpartum outcomes. Nurses are central to identifying and managing postpartum depression and anxiety through early screening, counselling, and facilitating access to mental health resources. This ensures timely intervention, reducing the long-term impact of these conditions. Breastfeeding support is another key area where nurses provide education, hands-on assistance, and innovative telehealth solutions to address challenges, empowering mothers to achieve their breastfeeding goals. For physical recovery, nursing guidance focuses on wound care, pelvic floor exercises, and structured postpartum exercise programs to promote healing and prevent complications. These interventions help restore physical well-being and improve mothers’ quality of life. A holistic nursing approach that combines education, emotional support, and the integration of modern technologies ensures optimal postpartum care. By addressing the multifaceted needs of new mothers, nurses foster their overall well-being and support a smoother transition into motherhood. This study explores how these targeted nursing interventions positively impact postpartum health, emphasizing the importance of a tailored, patient-centered approach in promoting maternal recovery and well-being.
Keywords: Breastfeeding; Mental health; Postpartum care; holistic nursing approach; physical recovery